Gene-environment interactions in Autism Spectrum Disorders (ASD) - Santos, João Xavier (2016)
Spectrum Disorder (ASD), is a heterogeneous neurodevelopmental disorder with na estimated global prevalence rate of 17:10000, and a male to female ratio of 4:1. Patients with ASD presente language and communication difficulties and stereotyped behaviours. Comorbidity with other disorders, such as Intelectual Disability, Fragile-X syndrome (FXS) epilepsy and tuberous sclerosis frequently occurs. ASD presents amultifactorial etiopathology, and genetic factos alone are not suficiente to explain how the syndrome arises, with recente studies establishing ASD heritability at approximately 50%. Pre-, peri- and post-natal exposure to toxic environmental factos has been implicated in the development of ASD. Involvement of epigenetic regulatory mechanisms has been suggested, supported by the occurrence of autistic symptoms in patients with disorders aris ing from epigenetic mutations, such as FXS. A polygenic and epistatic model is a strong hypothesis to explain ASD. The main goal of this project is to identify specific exposure patterns to environmental toxicants in children diagnosed with ASD and integrate the results with genetic and epigenetic data.